Management of newly diagnosed metastatic hormone‐sensitive prostate cancer: A survey of UK Uro‐oncologists. Issue 4 (16th February 2021) - Bahl, Amit; Crabb, Simon; Ford, Dan; Jones, Rob; Malik, Zaf; Mazhar, Danish; O'Sullivan, Joe; Payne, Heather
Abstract: Aim: To explore the practice and views of uro‐oncologists in the United Kingdom regarding their use of chemotherapy and androgen receptor‐targeted agents (ARTAs) in patients with newly diagnosed metastatic hormone‐sensitive prostate cancer (mHSPC). Methods: An expert‐devised paper or online questionnaire was completed by members of the British Uro‐oncology Group. Results: All respondents stated that they would offer patients with newly diagnosed mHSPC docetaxel and androgen deprivation therapy (ADT) if they were sufficiently fit to receive chemotherapy (this was the only option available at the time of the survey); 64% would strongly recommend docetaxel for those with high‐volume metastatic disease and 31% for those with low‐volume disease. Hypothetically, if both docetaxel and ARTAs were available in the United Kingdom for mHSPC, almost 65% of respondents would recommend an ARTA with ADT to these patients in at least one‐half of all cases, with the strongest recommendations to patients with high‐risk disease. Imaging for the response was conducted according to suspicion of disease progression, regardless of treatment, with the minority of clinicians recommending routine imaging. If a choice of therapy was available, docetaxel would be more likely to be offered to patients with liver or lung metastases, and ARTAs to patients with bone or lymph node only metastases. Almost all respondents would offer local radiotherapy to the primary tumour in patients with low‐volume disease. Conclusion: All the UK uro‐oncologists surveyed stated that they would offer docetaxel in combination with ADT to all newly diagnosed patients with mHSPC if fit enough for chemotherapy. ARTAs would be offered to many patients if available, especially those with high‐risk disease or those unfit to receive chemotherapy. Scanning was typically conducted following treatment only at the suspicion of disease progression.